The gut-immune axis in primary immune thrombocytopenia (ITP): a paradigm shifts in treatment approaches - Guo, Xuejun; Wang, Ke; Liu, Qianhui; Baran, Natalia; Ma, Wenxue (Frontiers in Immunology, 2025)
Primary immune thrombocytopenia (ITP) is an autoimmune disorder characterized by platelet destruction and impaired production, leading to bleeding risk. While immunosuppressive therapies are standard, many patients experience relapses or refractory disease, highlighting the need for novel approaches. Emerging evidence suggests the gut microbiota plays a role in immune regulation, yet its impact on ITP remains unclear. Dysbiosis has been linked to immune dysfunction in other autoimmune diseases, but whether it drives or results from immune dysregulation in ITP is debated. This review explores the gut-immune axis in ITP, focusing on microbiota-driven immune modulation, cytokine signaling, and platelet homeostasis. We assess microbiota-targeted interventions, including fecal microbiota transplantation (FMT), probiotics, and dietary modifications, while addressing key controversies and knowledge gaps. Advances in microbiome sequencing and artificial intelligence may facilitate personalized interventions. Standardizing microbiota-based diagnostics and validating their efficacy in clinical trials are crucial for their integration into ITP management. Bridging these gaps may lead to microbiota-driven strategies that enhance immune regulation and improve patient outcomes.